2018
DOI: 10.1111/bju.14480
|View full text |Cite
|
Sign up to set email alerts
|

The impact on oncological outcomes after radical prostatectomy for prostate cancer of converting soft tissue margins at the apex and bladder neck from tumour‐positive to ‐negative

Abstract: Conversion of the soft tissue margin at the prostate apex and bladder neck from histologically positive to negative improved the BCRFS and DMFS after RP for prostate cancer; however, the benefit of conversion was not apparent in patients in the high-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This occurrence is consistent with the recent finding from Pak et al (the paper is not included in the present review as it considers only SM from the apical and basal periprostatic tissue without including the NVB area). In the paper, they failed to find benefits of FS analysis and incremental resection in high‐risk patients, concluding that tumour biology is the major determinant of disease recurrence . However, given the constrained value of FS analysis of limited areas, one could argue that systematic sampling of the prostate surface would lead to a higher detection of PSM and thus improve conversion to a negative SM status.…”
Section: Evidence Synthesissupporting
confidence: 93%
“…This occurrence is consistent with the recent finding from Pak et al (the paper is not included in the present review as it considers only SM from the apical and basal periprostatic tissue without including the NVB area). In the paper, they failed to find benefits of FS analysis and incremental resection in high‐risk patients, concluding that tumour biology is the major determinant of disease recurrence . However, given the constrained value of FS analysis of limited areas, one could argue that systematic sampling of the prostate surface would lead to a higher detection of PSM and thus improve conversion to a negative SM status.…”
Section: Evidence Synthesissupporting
confidence: 93%
“…Frozen-section approaches and the 'NeuroSAFE' technique have been developed for this purpose [1][2][3][4]. These require a fully equipped laboratory, a pathologist inside the institution and take overall >30 min to perform.…”
mentioning
confidence: 99%
“…In these men, long‐term cancer outcomes are probably more related to risks of unsuspected metastatic disease rather than residual, microscopic cancer within the prostatic fossa. As suggested in this study , an initial PSM in high‐risk men, independent of ultimate NCSM, may be a surrogate for non‐localised disease and poorer outcomes; PSMs were found in 53% of men with pT3b. In low‐risk men, the issues are whether active surveillance is a more appropriate initial management strategy and that routine intraoperative frozen section analysis may not be worthwhile with a PSM rate of only 10%.…”
mentioning
confidence: 54%
“…The study by Pak et al. , published in this issue of the BJUI , reported that specimens with initial PSMs were converted to NSMs upon permanent specimen evaluation (NCSM) in 4.9% of 2013 men undergoing RP. In this subgroup, the 5‐year BCR‐free survival (BCRFS) rates did not differ from those observed in National Comprehensive Cancer Network (NCCN) low‐ and intermediate‐risk patients with an initially NSM.…”
mentioning
confidence: 99%
See 1 more Smart Citation